Ear, nose and throat examination and affecting factors in children: a school based-cross sectional study - Ayşegül Uludağ; Erkan Şahin; Fevzi Dereköy; Medine Kara; Murat Tekin; Satı Tekin; Yusuf Ertekin (SERNEV, 2016)
Introduction: In this study, we aimed to determine the most common pathologies by examining the ear, nose and throat (ENT) ofschool-aged population and the relation with the associated factors.Methods: A cross-sectional study was conducted between September-December 2013 at the primary and secondary schools in the citycenter of Çanakkale. A questionnaire was applied with the students' and parents' disease history and their habits. Ear, nose and throatexamination was performed and noted to the examination form.Results: A total of 1938 students were enrolled in the study. 1369 students (70.6%) were in primary schools, 569 (29.4%) were insecondary schools. Mean age of the students was 8.6 ± 2.3 years. The prevalence of tonsillar hypertrophy was 25.2%, prominent ear14.8%, otitis media 3.3%, anterior nasal deviation 10.4% respectively. Prominent ear were found more frequent in male children thanfemale children (p lt;0,001). There were no significant differences between children according to gender and the level of classes withhaving at least one ear-nose-throat pathology (p gt;0.05).Conclusion: Tonsillar hypertrophy, anterior nasal deviation, and otitis media were the most common pathologies in the school agedchildren respectively. The students' and the parents' medical histories and the parents' habits were not risk factors for having at leastone ear-nose-throat pathology.